Integrating DBpedia in multi-modality ontology news image retrieval - M. Khalid, Yanti Idaya Aspura; Noah, Shahrul Azman (2010)
The invention and usage of multimedia technology via digital camera, cellular phone, PDA and so on had increased the numbers of image retrieval in the Internet. Due to that, the research on the effectiveness of image retrieval system also has been growth not only to measure precision and recall, but also the user satisfaction. With realizing the demand in image retrieval, we tried to develop a prototype image retrieval system which integrates the low level features and high level concept in semantic gap. And our goal is to use a multi-modality ontology based system integrated with the knowledge sharing communities like DBpedia as our domain source which has an automated extraction methods to enhance our model and subsequently measure the effectiveness of our precision and recall.